7 - Gender and Corruption in Nigerian Politics - Amaechi D. Okonkwo (African Sociological Review, 2016)
This article explores the relationships, or the lack thereof, between gender and grand corruption in Nigeria. Methodologically, Butler’s theory of subject formation/performativity, and Kothari’s critique of participation, was used to interrogate selected Nigerian grand corruption literature and public indictment records. The objective was to tease-out and explain under-emphasized influences on grand corruption, such as the roles of godfathers, women’s political socialization and self-interests. Findings indicate that powerful political, cultural, military and industrial godfathers and mothers regulate aspirants’ selection, electoral funding, appointments and extraconstitutional protection from prosecution when they engage in grand corruption. Godfathers regulate political participation in a manner that encourage protégées fantasies about, and imitative adoption of their patrons’ corrupt worldviews and practices. Consequently, godfather political socialization, extra-constitutional pressures on office holders, and crass materialist accumulation interests of indicted female leaders seem to matter more than the gender binary.